Zvi Hecker - Paola Ardizzola (Vitruvio: International Journal of Architectural Technology and Sustainability)
Zvi Hecker (Krakow, 1931) is a Polish -Israeli architect and artist. After the Second World War years spent with his family in Samarkand where he first approached architecture by sketching monumental Islamic buildings, he began his studies in architecture in Krakow and completed them at the Technion in Haifa, where he graduated in 1955. Later he studied painting at the Avni Academy of Fine Arts in Tel Aviv. From 1960, with an office in Tel Aviv and until 1966 in association with A. Neumann and E. Sharon he designed residential complexes, synagogues, schools, and administrative buildings. In Israel, Tel Aviv, he realised his most iconic building, the Spiral House (1984-’89). In 1991 he opened a second atelier in Berlin after winning the competition for the Heinz Galinski school, the first Jewish school in the city after the Shoah. In the same year he took part in the Venice Architecture Biennale, as well in the 1996 and 2000 editions. In 1996 he was awarded the Deutscher Kritikerpreis and in 1999 the Rechter Prize for architecture.